Antipyretic Effect of Dexibuprofen Versus Ibuprofen in Children With Fever Caused by Upper Respiratory Tract Infection - Zhao, Chengsong; Zhao, Lin; Xie, Juanjuan; Wang, Xinli; Li, Changchong; Cheng, Huanji; Shen, Kunling (Clinical pharmacology in drug development, 2025)
Dexibuprofen is the pharmacologically active enantiomer of ibuprofen. However, its application as an antipyretic in children with fever caused by upper respiratory tract infection (URTI) requires more evidence. This study aimed to compare the antipyretic effect between dexibuprofen and ibuprofen in children with fever caused by URTI. Totally, 281 subjects were randomly assigned to the dexibuprofen (N = 142) or ibuprofen (N = 139) group at a 1:1 ratio. The subjects in the dexibuprofen or ibuprofen group were administered dexibuprofen + ibuprofen mimetic solution or ibuprofen + dexibuprofen mimetic solution 1-4 times per day. Dexibuprofen was considered at least as effective as ibuprofen if the lower limit of the 95% confidence interval (CI) for the mean difference in axillary temperature change at 4 hours was greater than -0.3°C. The axillary temperature change after 4 hours was 1.3°C in the dexibuprofen group and 1.4°C in the ibuprofen group. The difference in axillary temperature change at 4 hours was -0.10°C (95% CI, -0.27 to 0.09°C) between the 2 groups, and the lower limit of the 95% CI was greater than -0.3°C, suggesting a comparable antipyretic effect of dexibuprofen to ibuprofen. The axillary temperature change from baseline, rates of normal axillary temperature at 4 hours, time to normal axillary temperature, and disease-related symptoms at 24 or 48 hours were not different between the dexibuprofen and ibuprofen groups (all P  > .05). The incidence of adverse events did not differ between the 2 groups (all P > .05). In conclusion, dexibuprofen has a comparable antipyretic effect and safety profile to ibuprofen in Chinese children with fever caused by URTI.